2022
DOI: 10.3390/jcm11092587
|View full text |Cite
|
Sign up to set email alerts
|

Association between Early Mobilization in the ICU and Psychiatric Symptoms after Surviving a Critical Illness: A Multi-Center Prospective Cohort Study

Abstract: This is a prospective multicenter cohort study aiming to investigate the association between early mobilization (EM), defined as a rehabilitation level of sitting at the edge of the bed or higher within 72 h of ICU admission, and psychiatric outcome. Consecutive patients, admitted to the ICU for more than 48 h, were enrolled. The primary outcome was the incidence of psychiatric symptoms at 3 months after hospital discharge defined as the presence of any of three symptoms: depression, anxiety, or post-traumatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The physiotherapist intervened only on weekdays, and the nurse rehabilitated the patient in bed on weekends. The protocol established five levels of rehabilitation (level 1: passive exercise and respiration physiotherapy; level 2: active exercise; level 3: sitting; level 4: standing; and level 5: walking) based on the patient's medical condition [7,[20][21][22]. At each participating hospital, ICU practitioners or physiotherapists made the final determination concerning the degree of rehabilitation based on the patient's status and by referring to the protocol.…”
Section: Rehabilitationmentioning
confidence: 99%
“…The physiotherapist intervened only on weekdays, and the nurse rehabilitated the patient in bed on weekends. The protocol established five levels of rehabilitation (level 1: passive exercise and respiration physiotherapy; level 2: active exercise; level 3: sitting; level 4: standing; and level 5: walking) based on the patient's medical condition [7,[20][21][22]. At each participating hospital, ICU practitioners or physiotherapists made the final determination concerning the degree of rehabilitation based on the patient's status and by referring to the protocol.…”
Section: Rehabilitationmentioning
confidence: 99%
“…PICS causes physical disability, cognitive dysfunction, and psychiatric disorders that develop or worsen in patients after recovery from severe acute conditions, such as severe sepsis and acute respiratory distress syndrome [ 2 , 3 ]. Early rehabilitation is one of the preventive methods; however, further investigation into the specific clinical strength and activity time is needed [ 4 - 6 ]. In addition, in Japan, variations in early rehabilitation programs based on the hospital environment and the experience of the therapist still exist, and many hospitals have not created evidence-based protocols [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of early rehabilitation are widely reported, including the prevention of delirium [7], shortening the length of mechanical ventilation [8] and shortening the length of stay in the ICU [9,10]. Although relatively short-term results have been increasingly reported recently, data on the relationship between the mobilization level in critically ill patients and activity of daily living (ADL) independence at hospital discharge are still lacking [11][12][13]. Previous studies examined the mobilization level of ICU patients and reported that patients discharged home had higher ICU mobility score (IMS) scores at discharge from the ICU than patients discharged to the facility.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study investigated the relationship between the mobilization level during ICU admission and independence in ADL at hospital discharge. A post-hoc analysis of the EMPICS study [11], a multicenter prospective study of psychiatric symptoms in ICU patients three months after hospital discharge, was performed to investigate the association between the mobilization level during the ICU stay and ADL independence at hospital discharge.…”
Section: Introductionmentioning
confidence: 99%